The Research on the Composition Form of Landscape in Dunhuang Murals - Zhang, Jing; Phungamdee, Sakon (International Journal of Multidisciplinary in Management and Tourism, 2022)
From the scenery of Dunhuang murals, the characteristics and development of landscape painting in the Central Plains since the Wei, Jin, Northern and Southern Dynasties can be seen. Especially today, when none of the landscape paintings of well-known painters before the Tang Dynasty have been preserved, the scenery in Dunhuang murals has a unique value. Dunhuang landscape painting enriches the language of Chinese painting art, and its composition form has left a far-reaching impact. Like other paintings of Dunhuang murals, Dunhuang landscape painting is the artistic expression of important grottoes paintings. However, studying the composition forms of a nature landscape in Dunhuang murals at different historical stages can enrich and improve the research results on the landscape structure of Dunhuang murals. This paper studies the history of Dunhuang murals and the historical development process of landscape composition in Dunhuang murals and summarizes the composition characteristics and categories